2020
DOI: 10.3126/jpahs.v7i1.28858
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic services during COVID-19 lockdown at Patan Hospital, Nepal

Abstract: Introduction: The COVID-19 pandemic has paralyzed the world, including elective health care services. To prevent the spread of infection, most countries have gone into lockdown and adjustments have been made to provide urgent medical care, including Orthopaedic services. In accordance with the guidelines from worst affected countries and neighboring India, Patan Hospital followed instructions from Ministry of Health and Population to provide only urgent and semi-urgent Orthopaedic services. This study aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…They however did not have any cases of RTA owing to the lockdown. 22 Average injury surgery interval for trauma cases was 2.80 ± 3.38 days (range 0-15 days), which is similar to 3.12 days reported by Pradhan et al 22 This interval could be attributed to unavailability of vehicles, difficult terrains, other patients requiring optimization of medical or local condition for surgery and during latter half of lockdown, waiting for preoperative COVID-19 PCR reports. 22 Interestingly enough the average hospital stay for the admitted patients during the lockdown compared to the previous year was not very different.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…They however did not have any cases of RTA owing to the lockdown. 22 Average injury surgery interval for trauma cases was 2.80 ± 3.38 days (range 0-15 days), which is similar to 3.12 days reported by Pradhan et al 22 This interval could be attributed to unavailability of vehicles, difficult terrains, other patients requiring optimization of medical or local condition for surgery and during latter half of lockdown, waiting for preoperative COVID-19 PCR reports. 22 Interestingly enough the average hospital stay for the admitted patients during the lockdown compared to the previous year was not very different.…”
Section: Discussionsupporting
confidence: 77%
“…22 Average injury surgery interval for trauma cases was 2.80 ± 3.38 days (range 0-15 days), which is similar to 3.12 days reported by Pradhan et al 22 This interval could be attributed to unavailability of vehicles, difficult terrains, other patients requiring optimization of medical or local condition for surgery and during latter half of lockdown, waiting for preoperative COVID-19 PCR reports. 22 Interestingly enough the average hospital stay for the admitted patients during the lockdown compared to the previous year was not very different. Although we have tried to make the hospital stay shorter for all patient by discharging the patient from hospital earlier than we are used to, due to limited number of surgeries, surgeons, anesthetist and other human resources per day, limited number of ICU beds for patients who might have required ICU post-operatively, difficulty in obtaining necessary finances for surgeries due to limited opening of the banks, waiting for the reports of pre-operative nasopharyngeal swab for PCR for COVID-19, and one patient stayed for 89 days despite timely surgery, due to unavailability of vehicles to commute to and from the home.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Operated spine trauma cases were (10, 6.8%) similar to a study conducted at Patan Hospital, Nepal (2,5%). 19 Fall from height and tree due to increased agricultural activity during pandemic might have contributed to this result. In contrast to our study, a study from Italy showed a 50% reduction in spine trauma surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There is yet to be answers to these questions, however, this study offers some insight on the current situation in Kuwait regarding orthopedic injuries. Healthcare systems worldwide are facing challenges that they have never dealt with before [15][16] . In this study, we had lower numbers of the elderly population presenting to our departments.…”
Section: Interaction Between Gender and Curfew Variable And Their Effect On Place Of Orthopaedic Injury Discussionmentioning
confidence: 99%